The CYLD–PARP1 feedback loop regulates DNA damage repair and chemosensitivity in breast cancer cells - Miaomiao Zheng; Shuo Wang; Kexin Tang; Ruixue Kong; Xuemeng Wang; Jun Zhou; Yan Chen; Yijie Wang (Proceedings of the National Academy of Sciences, 2025)
Poly(ADP-ribose) polymerase 1 (PARP1) plays a crucial role in DNA repair and genomic stability maintenance. However, the regulatory mechanisms governing PARP1 activity, particularly through deubiquitination, remain poorly elucidated. Using a deubiquitinase (DUB) library binding screen, we identified cylindromatosis (CYLD) as a bona fide DUB for PARP1 in breast cancer cells. Mechanistically, CYLD is recruited by PARP1 to DNA lesions upon genotoxic stress, where it cleaves K63-linked polyubiquitin chains on PARP1 at residues K748, K940, and K949, resulting in compromised PARP1 activation. In a reciprocal manner, PARP1 PARylates CYLD at sites E191, E231, E259, and E509, thereby enhancing its DUB activity. Consequently, depletion of CYLD leads to increased efficiency in base excision repair and confers breast cancer cells with resistance to alkylating agents. Conversely, overexpression of CYLD enhances sensitivity to PARP inhibitors (PARPi) even in homologous recombination-proficient breast cancer cells. These findings offer unique insights into the intricate interplay between CYLD and PARP1 in DNA repair, underscoring the pivotal role of targeting this regulatory axis for breast cancer chemotherapy.